2022
DOI: 10.1094/phyto-04-22-0134-r
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus amyloliquefaciens PMB05 Increases Resistance to Bacterial Wilt by Activating Mitogen-Activated Protein Kinase and Reactive Oxygen Species Pathway Crosstalk in Arabidopsis thaliana

Abstract: Bacterial wilt caused by Ralstonia solanacearum can infect many crops, causing significant losses worldwide. The use of beneficial microorganisms is considered a feasible method for controlling this disease. Our previous study showed that Bacillus amyloliquefaciens PMB05 can control bacterial wilt through intensifying immune signals triggered by a pathogen-associated molecular pattern (PAMP) from R. solanacearum. It is still uncertain whether induction of the mitogen-activated protein kinase (MAPK) pathway dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The plant immune system is believed to rely on coordinated signaling pathways, including SA, JA, and ET pathways, to mount an effective defense response against pathogen attack [ 12 ]. Bacillus -primed ISR has been shown to involve the JA/ET and SA signaling pathways and multiple early signaling events, such as MAPK cascades and ROS [ 26 , 28 , 74 , 75 , 76 , 77 ]. In lettuce, B. amyloliquefaciens FZB42-produced surfactin, and other immunomodulatory CLPs triggered immunity against R. solani by inducing the expression of defense-related genes, including LsPDF1.2 , LsPR1, and LsLOX [ 28 ], while fusaricidin, purified from Paenibacillus polymyxa WLY78, induced SA-specific ISR to suppress Fusarium wilt in cucumber [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…The plant immune system is believed to rely on coordinated signaling pathways, including SA, JA, and ET pathways, to mount an effective defense response against pathogen attack [ 12 ]. Bacillus -primed ISR has been shown to involve the JA/ET and SA signaling pathways and multiple early signaling events, such as MAPK cascades and ROS [ 26 , 28 , 74 , 75 , 76 , 77 ]. In lettuce, B. amyloliquefaciens FZB42-produced surfactin, and other immunomodulatory CLPs triggered immunity against R. solani by inducing the expression of defense-related genes, including LsPDF1.2 , LsPR1, and LsLOX [ 28 ], while fusaricidin, purified from Paenibacillus polymyxa WLY78, induced SA-specific ISR to suppress Fusarium wilt in cucumber [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on similar line suggested ROS mediated activation of MAPK pathway during plant-pathogen interaction (Pacheco-Trejo et al, 2022;Chuang et al, 2022). Interestingly, in other plants as well, Rboh have been shown to be involved in responses to microbial infection (Morales et al, 2016, Chaung et al, 2022.…”
Section: Involvement Of Aarboha and Aarbohc During Agarwood Formation...mentioning
confidence: 96%
“…The determination of the disease index was based on the scales of developed symptoms in a 4 cm 2 (2 cm × 2 cm) area in the middle of the leaf (0: no disease symptoms; 1: less than 5 yellowing spots; 2: more than five yellowing spots; 3: more than 5 lesions with necrotic symptoms; 4: healed necrotic lesions; 5: healed necrotic lesions with shot hole.) The disease severity of each leaf was calculated using the following formula: [18]. The disease severities were calculated from five sets of plants in each treatment.…”
Section: Effect Of B Amyloliquefaciens Pmb04 On the Control Of Bacter...mentioning
confidence: 99%